2020
DOI: 10.12890/2020_001748
|View full text |Cite
|
Sign up to set email alerts
|

Can Lung Ultrasound be Used to Screen for Pulmonary Embolism in Patients with SARS-CoV-2 Pneumonia?

Abstract: Thromboembolic disease is strongly associated with, or even an integral part of, COVID-19 pneumonia. Indeed, endothelial/microvascular damage to pulmonary capillaries seems to be the main trigger of the pneumonia. Here we report a case of pulmonary embolism in a COVID-19 patient with an atypical clinical presentation. Blood gas analysis and lung ultrasound allowed the correct diagnosis to be reached.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…COVID-19 patients present a wide range of clinical conditions, ranging from asymptomatic infections, minimal symptoms (the majority of patients) to fatal respiratory distress (ARDS) [ 1 ]. Data in published literature have shown that about a quarter of COVID-19 infected patients experienced thrombocytopenia and about half of these patients succumb to infection due to coagulopathy [ 3 , 4 ]. The mechanisms leading to thrombocytopenia are not yet well known.…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 patients present a wide range of clinical conditions, ranging from asymptomatic infections, minimal symptoms (the majority of patients) to fatal respiratory distress (ARDS) [ 1 ]. Data in published literature have shown that about a quarter of COVID-19 infected patients experienced thrombocytopenia and about half of these patients succumb to infection due to coagulopathy [ 3 , 4 ]. The mechanisms leading to thrombocytopenia are not yet well known.…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes, post-COVID-19 vaccine supraclavicular and axillary lymph nodes may mimic pathological lymph nodes. Ultrasound (US) examination may represent the firstline imaging method due to its speed, low cost and repeatability and has already played a central role in this pandemic [15][16][17]. Sonologists should be aware that a recent anti-COVID-19 vaccine can present an etiology of supraclavicular and axillary lymph nodes with suspicious US features.…”
Section: Introductionmentioning
confidence: 99%
“…A direct assessment of the pulmonary hilar vessels and its branches is not possible on ultrasound due to the generation of artifacts that prevent an "anatomical" visualization of the lung. 19 However, some transthoracic echocardiographic scans are able to highlight the initial portion of the pulmonary artery, and less frequently, the two main branches; the transthoracic method can go no farther. 7 The main contribution of LUS in a patient with pulmonary thromboembolism is the visualization of a peripheral pulmonary infarction, 7,19 which is the ultimate outcome of the pathophysiological process that leads to an ischemic alteration of the lung parenchyma.…”
Section: Basics Of Lung Ultrasoundmentioning
confidence: 99%
“…Venous thromboembolism can manifest in peculiar ways in patients with coronavirus disease 2019 (COVID-19). 19,52 Pulmonary infarction may stem from a "local" inflammatory response in the lung-which may result in a hypercoagulable state (so-called endotheliopathy)-rather than peripheral venous thrombosis. 19,52 This mechanism can result in widespread areas of in situ pulmonary thrombosis and subsequent infarction.…”
Section: Role Of Contrast-enhanced Ultrasoundmentioning
confidence: 99%